Beliefs about Breast Cancer among Women in the Western Amazon: A Population-Based Study - Schilling, Marla Presa Raulino (Asian Pac J Cancer Prev, 2019)
OBJECTIVE: Evaluate the beliefs about the risk factors for breast cancer in a population of women from the western Amazon and determine the factors associated with the higher belief scores presented by this population. METHODS: A population-based cross-sectional study included 478 women aged >40 years residing in Rio Branco, Acre, Brazil. An American Cancer Society questionnaire was applied to assess the knowledge, attitudes, and beliefs about breast cancer. RESULTS: The main beliefs about the risk factors for breast cancer were breast trauma (95%), use of underwire bra (58.5%), and a high number of sexual partners (55.5%). Women from younger age groups presented higher belief scores (Bcoefficient: –0.04, 95% CI: –0.07; –0.01) than those of women from older age groups. A strong association was noted between high knowledge scores of risk factors and signs/symptoms of the disease and high belief scores in the study group (Bcoefficient:0.33;95%CI:0.28;0.38). CONCLUSION: The results indicate the existence of important beliefs related to the risk factors for breast cancer. Women from younger age groups, women who have seen a gynecologist in the past 2 years, and women who had more knowledge about the risk factors and signs and symptoms of breast cancer had higher belief scores.